Participatory Rangeland Management: Inclusive learning and reflections from Kenya - Bullock, Renee; Majiwa, Hamilton; Okoth, Joshua; Mukalo, Irene Aloo; Nganga, Irene; DuttaGupta, Tanaya (International Livestock Research Institute, 2025)
AICCRA supported the scaling of PRM in Kenya and activities to strengthen the inclusive governance of rangeland management institutions. This infonote documents activities carried out in Baringo County with Paka Hills Community Rangeland and Irong Conservancy committee members. The overarching aim of the activities was to increase learning and networking around adaptation practices and to reflect upon PRM performance and plan future rangeland activities.